Human Rights Approach in Environment Law Enforcement based on Law Number 23/2009 (Research, Society and Development, 2019)
Individual has the same rights to have prosperity life including the right to have healthy life. In this research, the objective of the study is to discuss about the enforcement of environmental law based on Law Number 32 of 2009 about Environmental Protection and Management based on a human rights. Using The results found that the administrative punishment is a quick way and appropriate to stop the violation in environment. It is due to the punishment is given without going through court processing. Administrative punishment is referred to the violation not to the person. In addition, imposition of administrative punishment is not aimed to punish the violator, but it is more concern to the recovery the situation (reparatoir).